THAI STUDENTS’ STRATEGIES IN LEARNING ENGLISH VOCABULARY - Mahardika, Agustine Andriana Ayu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
English is the most learned language by EFL learners in multilingual countries, including Thailand. To communicate with others in English fluently, students have to learn English vocabulary. Since learning English vocabulary is difficult, it can be overcome with suitable learning strategies. One research question to be answered in this research is “What are the learning strategies undertaken by Thai students to learn English vocabulary?” This mixed-method research employed a Likert-scale questionnaire distributed to 18 Thai students, and the FGD interview was conducted via Zoom with 3 Thai students. The questionnaire contained 21 items of Likert-scale statements and two open-ended questions. The findings showed that the strategy they frequently use is the metacognitive strategy, while the strategy they rarely use is the memory strategy. It is recommended that future researcher interested in expanding this topic do extensive research to determine its trustworthiness and provide further information about the topic.